2013
DOI: 10.1177/0961000612470278
|View full text |Cite
|
Sign up to set email alerts
|

The effect of public library use on the social capital of rural communities

Abstract: This paper reports on a study that investigated the relationship between social capital and public library use in small towns in Ontario, Canada. Comparisons were also made with the findings of a similar study that was conducted in a medium-sized urban centre. Data for this study were collected through questionnaires administered to both library users and non-users and interviews with library staff and frequent library users. Both Robert Putnam's and Nan Lin's conceptualizations of social capital informed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 23 publications
0
7
0
4
Order By: Relevance
“…The quantitative results of the study have been reviewed in a separate article, which focuses largely on the first question (Johnson and Griffis, forthcoming). The quantitative data strongly suggest that rural library use does not play a significant role in building or maintaining levels of social capital in small towns in Southwestern Ontario.…”
Section: Research Objective and Methodologymentioning
confidence: 99%
“…The quantitative results of the study have been reviewed in a separate article, which focuses largely on the first question (Johnson and Griffis, forthcoming). The quantitative data strongly suggest that rural library use does not play a significant role in building or maintaining levels of social capital in small towns in Southwestern Ontario.…”
Section: Research Objective and Methodologymentioning
confidence: 99%
“…However, owing to the characteristics of the communities that public libraries served, any two public libraries might not have the same influence on social capital. A Canada study showed that public libraries in rural communities had no significant association with social capital owing that the social network in a rural community was comparatively tighter than in an urban community (Johnson and Griffis 2014). In contrast with a rural community, a public library in an urban community has more influence on social capital because the latter provides relatively higher quality resources for low-income inhabitants, increasing their connection with the public library and then form the community cohesiveness.…”
Section: Public Library and Social Capitalmentioning
confidence: 99%
“…Šios koreliacijos yra ryškesnės bendruomenės nei individo lygmeniu (Anheier ir kt., 2017;Azevedo, 2016;Beaudoin, 2009;Brown ir kt., 2012;Delaney, Keaney, 2005;Freitag. 2003;Fujiwara ir kt., 2014;Hoffman, Appiah, 2008;Hoye ir kt., 2015;Yun ir kt., 2018;Johnson, 2010;Johnson, Griffis, 2013;Larson ir kt. 2006;Lee ir kt., 2016;Lewicka, 2005;Lizardo, 2006;Okayasu ir kt., 2010;Polzella, Forbis, 2013;Romer ir kt., 2009;Seippel, 2006;Wilson, Musick, 1997).…”
Section: Dalyvavimo Kultūroje Poveikio Socialiniam Kapitalui Matavimounclassified